Proteinase-3 and myeloperoxidase serotype in relation to demographic factors and geographic distribution in anti-neutrophil cytoplasmic antibody-associated glomerulonephritis. Issue 2 (30th April 2018) - Weiner, Maria; Bjørneklett, Rune; Hrušková, Zdenka; Mackinnon, Bruce; Poulton, Caroline J; Sindelar, Leo; Mohammad, Aladdin J; Eriksson, Per; Gesualdo, Loreto; Geetha, Duvuru; Crnogorac, Matija; Jayne, David; et al.
Abstract: Background: In anti-neutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis, antigen specificity varies between myeloperoxidase (MPO) and proteinase 3 (PR3). This has been reported to vary in relation to age, gender, geography and extrarenal manifestations. However, studies are difficult to compare as criteria for inclusion vary. The aim of this study was to investigate the relationship between ANCA serotype, latitude, ultraviolet (UV) radiation levels, age, gender and renal function at diagnosis in a large study with uniform inclusion criteria. Methods: Patients with biopsy-proven ANCA-associated glomerulonephritis were identified from regional or nationwide registries in 14 centres in Norway, Sweden, the UK, the Czech Republic, Croatia, Italy and the USA during the period 2000–13. UV radiation levels for 2000–13 in Europe were obtained from the Swedish Meteorological and Hydrological Institute. Results: A total of 1408 patients (45.2% PR3-ANCA) were included in the study. In univariable analysis, PR3-ANCA was significantly associated with male gender odds ratio [OR] 2.12 [95% confidence interval (CI) 1.71–2.62], younger age [OR per year 0.97 (95% CI 0.96–0.98)] and higher glomerular filtration rate [OR per mL/min 1.01 (95% CI 1.01–1.02); P < 0.001] at diagnosis but not with latitude or UV radiation. In multivariable logistic regression analysis, latitude and UV radiation also became significant, with higher odds for PR3-ANCA positivity at northern latitudes/lower UV radiation levels. However, the latitudinal difference in MPO:PR3 ratio is smaller than differences previously reported concerning microscopic polyangiitis and granulomatosis with polyangiitis. Conclusions: The ratio between PR3-ANCA and MPO-ANCA varies in glomerulonephritis with respect to age, gender, renal function and geographic latitude/UV radiation levels.